TYPES OF ACADEMIC INTERNET-RESOURCES FOR IT STUDENTS' INDIVIDUAL WORK MANAGEMENT - O. Glazunova; T. Voloshyna (Kherson State University, 2014)
Individual work is one of the main forms of organization of academic process for students of IT specialties. Main practical professionally oriented skills and abilities are retained only due to students' hard individual work while doing tasks in programming, algorithmization, designing etc. development of effective academic resources will help students to work individually as well as comfortable ways of delivering such materials with the help of Internet guarantees enhancing the quality of studies. Information and educational resources for independent work of students today are one of the most effective means. The technique of creating and using these tools requires constant research through the rapid development of new information technologies. The present article describes the most effective tools and technologies for creating online resources for self-study of IT students, grounded methods of their use in the educational process. The most commonly used tools for formal and informal components of independent work are identified: professionally-oriented sites, massive open online courses, blogs programmers professionally groups on social networks, news sites, and so on. Studies show a significant improvement of independent work of students on the study material by using video tutorials.